The Effect of Company Size and Financial Ratios on the Level of Financial Distress in Banking Sector - Endarto, Eko Agus Prasetyo; Mulyono, Mulyono (ProBisnis : Jurnal Manajemen, 2024)
Banking is an essential sector that improves a country's economy. The world economy has been shaken since the onset of the COVID-19 pandemic, along with global conflicts, which have caused many problems for banks. Banks in Indonesia also feel the impact, so banks need to survive well so as not to experience losses that lead to financial difficulties. This study uses financial ratios and company size to measure the effect of financial distress using the Altman Z-Score. The sample used is a bank listed on the Indonesia Stock Exchange from 2018 – 2022. Data processing using multiple regression with the help of SPSS statistical software. The results of this study found that the ratio of BOPO, ROA, and SIZE had a significant effect on financial distress. In contrast, the NPL, LDR, and BETA ratios did not have a significant effect. The following study can include environmental, social, and governance variables or ESG so that the application of sustainability activities can be measured in relation to financial distress.